Advancing university-business cooperation in the Mediterranean area - Vera Amicarelli; Giuseppina Miuli; Christian Bux; Raluca Mariana Grosu (Amfiteatru Economic Journal, 2022)
The present paper aims at investigating potential strategies for advancing university-business cooperation (UBC) in the Mediterranean area. The paper was developed from a real practical problem consisting of a poor UBC, as observed at the University of Bari Aldo Moro (Bari, Italy). In a more particular case, this was translated into a wall perceived by both universities and companies, a wall that was represented by the lack of transparency and the temporal mismatch between the skills of students and the needs of entrepreneurs. In an innovative manner, in the light of the Design Thinking approach, the research addresses potential solutions to solve the identified practical problem, through the lenses of the Double Diamond model. Each step of the model revealed invaluable insights for better understanding the analysed problem and for providing coherent measures to improve UBC. Particularly, it was revealed that collaborations between the businesses and the university must become an integral part of research projects, as well as a key element of academic publications and teaching. Also, strong networks between representatives from the academic and business environments should be enhanced. In a more specific perspective, three main directions (prototypes) were explored in the paper: (a) design of relax and convivial areas which allow students and entrepreneurs to meet; (b) organization of meetings between students and entrepreneurs in a human-centred perspective; and (c) implementation of real synergies between companies and students, based on meetings, formal agreements, mutual knowledge and win-win performances. The paper brings new knowledge on UBC, especially in the Mediterranean area, of both practical and theoretical relevance.
Keywords: A20; M10; 330; Design Thinking; Double Diamond; Mediterranean area; university-business cooperation